Higher depression rates and similar cardiovascular comorbidity in psoriatic arthritis compared with rheumatoid arthritis and diabetes mellitus. (December 2020) - Fragoulis, George E.; Evangelatos, Gerasimos; Tentolouris, Nikolaos; Fragkiadaki, Kalliopi; Panopoulos, Stylianos; Konstantonis, George; Iliopoulos, Alexios; Chatzidionysiou, Katerina; Sfikakis, Petros P.; Tektonidou, Maria G.
Background: We explore the spectrum of comorbidities in psoriatic arthritis (PsA) patients in comparison with other high comorbidity-burden diseases like rheumatoid arthritis (RA) and diabetes mellitus (DM). Methods: Two hundred and fifteen PsA patients, cross-sectionally collected from two tertiary hospitals, were compared with 215 RA and 215 DM patients (age/sex-matched, similar disease duration). Cardiovascular risk factors [hypertension, current smoking, hyperlipidaemia, obesity (body mass index (BMI) ⩾30)], coronary artery disease (CAD), stroke, major adverse cardiac events (MACEs; combined CAD and stroke), depression, osteoporosis and malignancies were recorded. Odds ratios (ORs) for stroke, CAD and MACE were adjusted for age, sex, hypertension, smoking, hyperlipidaemia, BMI, glucocorticoids use and those for depression were adjusted for age, sex, disease duration, skin involvement and smoking. Within the PsA group, associations between comorbidities and demographic/clinical features were assessed. Results: Depression [OR (95% confidence interval (CI)): 3.02 (1.57–5.81)], obesity [OR (95% CI): 2.83, (1.65–4.86)] and hyperlipidaemia [OR (95% CI): 1.96 (1.32–2.90)] were more prevalent in PsA compared with RA, while no differences were observed for CAD, stroke, MACE and malignancies. Depression [OR (95% CI): 4.85 (2.37–9.93)] and osteoporosis [OR (95% CI): 6.22 (1.33–29.2)] were more common in PsA than in DM. Hypertension, but not the other cardiovascular risk factors, was more frequent in DM [OR (95% CI) 0.49 (0.33–0.74)]. However, prevalence of stroke, CAD and MACE did not differ between PsA and DM. Within PsA group, depression was associated with age [OR (95% CI): 1.03 (0.99–1.06)], female sex [OR (95% CI): 3.47 (1.51–7.99)] and smoking [OR (95% CI): 2.78 (1.31–5.88)] while MACEs were associated with age [OR (95% CI): 1.08 (1.00–1.17)], male sex [OR (95% CI) for females: 0.26 (0.06–1.23) and hypertension [OR (95% CI): 6.07 (1.12–33.0)]. No differences were recorded in comorbidities between the different PsA phenotypes. Conclusion: Depression was more prevalent in PsA compared with RA and DM, while cardiovascular comorbidity was comparable to both groups, supporting the need for their assessment and management.